In the shadow of the palms : more-than-human becomings in West Papua - Chao, Sophie (Duke University Press, 2022)
"Drawing on long-term ethnographic fieldwork and prior human rights advocacy in the Indonesian-controlled region of West Papua, In the Shadow of the Palms explores how deforestation and monocrop oil palm expansion reconfigure the multispecies lifeworld of Indigenous Marind communities through its effects on the landscape, time, personhood, and dreams. Working with and across species categories and hierarchies, the book highlights how the proliferation of industrial monocrops subverts the futures and relations of some lifeforms while opening new horizons of possibility for others. Sophie Chao situates these dynamics within West Papua's violent and volatile history of political colonization, ethnic domination, and capitalist incursion. By approaching cash crops as both drivers of destruction and subjects of human exploitation, the book makes a compelling argument for rethinking capitalist violence as a multispecies act. Taking oil palm as its central protagonist, it makes a timely contribution to our understanding of human-environment relations in an age of radical ecological change."--